Development of Brand Awareness Through Social Media Marketing of UMKM Fried Chicken in Medokan Ayu Surabaya - Kartika Maulida Hindrayani; Tresna Maulana F; Imelda Widya Ningrum; Aisyah Kirana Putri Isyanto (Future Science, 2023)
The development of information technology has many benefits for partner actors to make processes automatic in increasing productivity and marketing. Marketing management in today's technological world requires a strategy for disseminating information and expanding marketing targets. Skills in using social media as a digital marketing tool can increase consumers or customers' ability to recognize and remember a product being promoted. This will also increase brand awareness. The method used is a development method with observation steps in the field, identifying partner’s problems and weaknesses, offering solutions to partners, designing training materials, implementing training material designs and integrating materials. The results of the development of brand awareness using social media, we use Instagram Platform and Google Review. Hopefully this will raise awareness of the UMKM Fried Chicken with its franchise located in Medokan Ayu. Good relations, complete explanations and clear communication with partners will support marketing development through brand awareness through social media.